Aplikasi Bioteknologi Fermentasi Tepung Biji Trembesi Samanea saman Dalam Pakan Terhadap Pertumbuhan dan Sintasan Ikan Nila (Oreochromis niloticus) - Kasman; Fatihatul Nikma; Nurhayati; Magfiratun; Yessi Revina Beqi; Asni Anwar; Murni; Akmaluddin (Faculty of Science and Technology University Ibrahimy, 2022)
The specific objective of this research is to obtain appropriate technology that can be applied in increasing the growth and survival of tilapia seeds as an effort to maximize the use of rain Tree seeds through fermentation biotechnology using yogurt, to increase tilapia production nationally. This study used a completely randomized design (CRD) with 4 treatments each repeated 3 times. For what was tested was treatment A (the content of fermented rain tree flour without using yogurt (control)), B (the content of fermented tamarind flour with yogurt 4 ml/kg of feed), C (the content of fermented rain tree flour with yogurt 6 ml/kg of feed) and D (fermented rain tree flour with yogurt 8 ml/kg feed). The results showed that fermented rain tree seeds using yogurt with different doses had a significant effect (p<0.05) on the growth and survival of tilapia. Further tests using multiple distances (Duncan) showed differences between treatments. The highest growth was obtained in treatment B (yogurt dose 4 mL/kg) of 21.51gr, followed by treatment A (control) 20.24gr, treatment C (yogurt dose 6 mL/kg) 19.57gr, and the lowest was treatment D (8 mL/kg). ) 19.25gr. The highest survival rate was obtained in treatment B (yogurt dose 4 mL/kg) of 88%, followed by treatment A (control) 81.33%, treatment C (yogurt dose 6 mL/kg) 78.67%, and treatment D (yogurt dose 8 mL/kg). ) with the same value of 78.67%. Based on the results of the study, it can be concluded that the application of fermented rain tree flour with yogurt 4 ml/kg in feed can increase the growth and survival of tilapia. Key Word: Rain tree, biotechnology, Oreoshromis niloticus, Feed.